Evolving Training Methods and Technology Integration in Hospitality Management Education: A Conceptual Review - Kumar, Ravi; Khatter, Ajay (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2026)
This review examines the evolution of training methodologies and the integration of emerging technologies in hospitality management education, with particular emphasis on the Indian context. The study synthesises existing scholarly literature from hospitality education, human resource development, educational technology, and adult learning theories to examine the transition from traditional training models towards experiential, competency-based, and technology-enhanced learning approaches. A structured literature review approach was adopted using academic sources identified through databases including Scopus, Google Scholar, and hospitality-related journals. The selected literature was analyzed thematically to identify major developments, opportunities, and challenges associated with modern hospitality training. The findings highlight that effective hospitality education requires a balanced integration of experiential learning, emotional intelligence development, digital technologies such as virtual reality and artificial intelligence, and stronger alignment between academic curricula and industry requirements. The review identifies challenges related to technological investment, faculty preparedness, infrastructure limitations, and the need to maintain the human-centered nature of hospitality service. The paper contributes practical recommendations for hospitality institutions seeking to develop future-ready graduates capable of adapting to an increasingly digital and service-oriented industry.
Keywords: Hospitality management education; training methodologies; experiential learning; educational technology; artificial intelligence; hospitality workforce development